The Schur ℓ1 Theorem for Filters - Lopez, Antonio Aviles; Salinas, Bernardo Cascales; Kadets, Vladimir; Leonov, Alexander (Журнал математичної фізики, аналізу, геометрії, 2007)
We study the classes of filters ℱ on ℕ such that the weak and strong ℱ-convergence of sequences in ℓ1 coincide. We study also an analogue of ℓ1 weak sequential completeness theorem for filter convergence. Mathematics Subject Classification: 46B25, 54A20.